MODEL PENGELOLAAN SUMBER DAYA PERIKANAN TANGKAP BERBASIS RESOLUSI KONFLIK - Rusmilyansari Rusmilyansari; B. Wiryawan; J. Haluan; D. Simbolon (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2010)
Capture fishery conflicts is one issue that requires serious attention. The government has tried to overcome the fisheries conflicts by issuing various regulations, but the results have not been effective. This study aims to create a model of conflict management. The research method used the perception survey. Primary data collected through using a structured questionnaire done purposively to some respondents. Analytical survey of perceptions using SEM (Structural Equation Modeling). The results showed: (i) Simultaneously, the better the ability to identify the causes of the conflict the better the ability to determine the conflict resolution techniques. Furthermore, the better the ability to determine an appropriate conflict resolution techniques will increase support for the management of fisheries resources is responsible (ii) Partially causes of conflict are determined by the indicators of competition, opposition, economic, actors and cultural (ii) facilitation techniques, negotiation, litigation and avoidance can be used as an appropriate conflict resolution techniques (iii) an understanding of community participation and conservation of fishery resources determines the creation of sustainable fisheries resource management is responsible.